ENHANCING EFL IN-SERVICE TEACHERS’ TEACHING SKILL THROUGH THE ROLE OF VIDEO-BASED REFLECTIONS - Zainuddin Zainuddin; Sunu Dwi Antoro; Herri Mulyono; Nani Solihati; Rosalina Rosalina; Ferawati Ferawati (University of Kuningan, 2022)
The essential purpose of the research was to examine EFL in-service teachers’ perceptions after watching their teaching video recording. This research attempted to explore more insight of the video-based reflections roles focusing on teacher development. The research applied a qualitative design with eight EFL in-service teachers as participants. The data were conducted through semi-structured interviews, journal reflective, and video recording. All these data were then analyzed using thematic analysis. The result demonstrates that video-based reflection is an accomplished way to gain self-evaluation. These in-service teachers have gained new views, and have chances to analyze both deficiencies and potencies using video-based reflections in their teaching experiences. Conclusively, video-based reflections can promote teachers’ professional development.